1998
DOI: 10.1055/s-0037-1615023
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Thrombopoietin Level Measurements in Thrombocytopenia

Abstract: SummaryIt has been reported that blood trombopoietin (TPO) levels can discriminate between thrombocytopenia due to increased platelet destruction and decreased platelet production. With our TPO ELISA and a glycocalicin ELISA we analysed a large group of patients in detail and could confirm and amplify the above notion in detail.TPO levels were determined in plasma from 178 clinically and serologically well-defined thrombocytopenic patients: 72 patients with idiopathic autoimmune thrombocytopenia (AITP), 29 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 24 publications
4
63
1
9
Order By: Relevance
“…Trials are in progress to clarify the relative merits of each form of treatment, although, increasingly, it is desirable to avoid fetal sampling, if feasible. We and others detected normal or only slightly elevated Tpo levels in ITP patients (7)(8)(9)(10). We now find that Tpo levels in NAIT fetuses are also normal or only slightly elevated compared with levels in nonthrombocytopenic age-matched controls.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Trials are in progress to clarify the relative merits of each form of treatment, although, increasingly, it is desirable to avoid fetal sampling, if feasible. We and others detected normal or only slightly elevated Tpo levels in ITP patients (7)(8)(9)(10). We now find that Tpo levels in NAIT fetuses are also normal or only slightly elevated compared with levels in nonthrombocytopenic age-matched controls.…”
Section: Discussionsupporting
confidence: 55%
“…After binding, Tpo is eventually destroyed together with the platelets. We and others have shown the diagnostic value of measurement of plasma Tpo levels for discrimination between thrombocytopenia caused by megakaryocyte and platelet production failure (highly elevated Tpo levels) and thrombocytopenia caused by elevated platelet destruction observed in autoimmune thrombocytopenia (normal or only slightly elevated Tpo levels) (7)(8)(9)(10)(11). In the latter disorder, megakaryocyte numbers in the marrow are normal or increased, as is platelet production.…”
mentioning
confidence: 99%
“…These clearly showed that, under conditions of thrombocytopenia, the platelet RNA content correlated directly with megakaryocytic activity [9]. The parameters of platelet production and turnover rate have also been studied using platelet lifespan [14], glycocalicin index [15], and thrombopoietin level [16]. However, the platelet lifespan is not widely used because of problems associated with the manipulation of platelets and the use of radioactivity [17].…”
Section: Discussionmentioning
confidence: 99%
“…The actual quantity of HIV in circulation was evaluated by estimation of plasma HIV-RNA levels using the polymerase chain reaction (Amplicor HIV-1 Monitor test, limit of detection: 400 HIV-1RNA copies/mL, Roche Diagnostics). TPO levels were measured by an enzyme-linked immunoabsorbent assay (ELISA) [20,21]. According to this method, serum TPO levels measured in 137 healthy donors ranged from 13.6 to 108 AU (2.5th-97.5th percentile; these levels average 3.4-fold higher than plasma TPO levels in the same individuals).…”
Section: Laboratory Testingmentioning
confidence: 99%